Adverse event profile differences between maribavir and valganciclovir: findings from the FDA adverse event reporting system - Teng, Haolin; Zhang, Shengnan; Yu, Jinyu; Li, Faping (Frontiers in Pharmacology, 2025)
BackgroundMaribavir and valganciclovir are pharmacotherapeutic options utilized in the management of cytomegalovirus (CMV) infection post-transplantation. Despite their established utility, a comprehensive assessment of their safety profiles in real-world settings remains lacking, particularly with regards to long-term safety outcomes within a sizable cohort.ObjectiveThe study aims to analyze the adverse event (AE) profiles of maribavir and valganciclovir using data from the U.S. Food and Drug Administration Adverse Event Reporting System (FAERS). This endeavor seeks to juxtapose their respective association strengths and furnish clinicians with pertinent clinical reference points.MethodsEmploying a methodological framework involving the filtration of the FAERS database by specific drugs (maribavir and valganciclovir), AEs attributed to each agent were meticulously cataloged. We applied various disproportionation analysis techniques, including the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN) and multi-item gamma Poisson shrinker (MGPS) algorithms, to identify and quantify potential signals of AEs associated with maribavir and valganciclovir.ResultsThere were 999 and 3,454 reports for maribavir and valganciclovir, respectively. Maribavir was primarily associated with the following AEs: dysgeusia (133, 4.07%), taste disorder (127, 3.89%), death (120, 3.67%), fatigue (105, 3.21%), and diarrhea (69, 2.11%). In contrast, the most notable AEs linked to valganciclovir included death (260, 2.59%) and neutropenia (246, 2.59%), leukopenia (175, 1.74%), diarrhea (117, 1.17%), and thrombocytopenia (113, 1.13%). Remarkably, death emerged as an unexpected AE signature for both agents. Key associations were elucidated, notably taste disorder (ROR: 65.23) for maribavir and CMV colitis (ROR: 152.26) for valganciclovir, accentuating distinct AE propensities. Additionally, median onset times for AE manifestation were delineated, with maribavir exhibiting a median onset time of 40 days, compared to 28 days for valganciclovir-associated AEs.ConclusionThis comprehensive analysis of FAERS data enhances our understanding of the safety. These findings hold implications for ongoing clinical surveillance efforts and provide a foundational basis for subsequent investigations into the safety profiles of these agents.